Movable Inn. The Rural Jewish Population of Minsk Guberniya in 1793-1914 - Kalik, Judith (De Gruyter, 2018)
The book presents the results of a systematic survey, the first of its kind, on the rural Jews in the Minsk Guberniya, from its establishment as a major administrative unit within the Russian Empire in 1793, to the outbreak of the First World War in 1914.
English
Keywords: family structure; Jews; demography; culture; landlords; Belarus; genealogy